Pendampingan Penulisan Karya Tulis Ilmiah Bagi Guru MAN 2 NGANJUK - Hapsery, Alfisyahrina; Pramesti, Wara (Jurnal Visi Pengabdian Kepada Masyarakat, 2024)
Education emphasizes the importance of writing skills and reading literacy for students, with writing as a means to express ideas and reading literacy as the primary key. Scientific paper writing (KTI) serves as a platform to develop students' writing skills with teacher guidance, especially through extracurricular activities such as the Teen Scientist Group (KIR). However, lack of motivation and guidance leads to a decline in students' interest in KTI. Reading literacy, from both traditional and social media sources, and guidance from skilled teachers can increase students' interest and abilities in writing KTI. KTI guidance for teachers at Madrasah Aliyah Negeri (MAN) 2 Nganjuk is part of community service efforts to improve students' reading and writing literacy. Implementation methods include material presentations, literature studies, KTI creation simulations, and direct guidance. As a result, teachers show high enthusiasm in learning and proposing KTI ideas, focusing on current issues. This activity successfully enhances teachers' interest and skills in guiding students in writing KTI.